Extended Exergy Accounting analysis of IGCC process - Determination of environmental remediation cost of refinery and coke processing waste - SEÇKİN, CANDENİZ (ELSEVIER SCI LTD, 2016)
This study focuses on determination of environmental remediation cost of energy production from refinery and coke processing solid waste by means of Extended Exergy Accounting methodology. Environmental remediation cost is a novel concept which is proposed by the method of Extended Exergy Accounting and it represents the cumulative resource equivalent of the pollutants to convert them into ideal, zero-impact disposal. In this study, refinery and coke processing waste is subjected to integrated gasification combined cycle which is a gasification and combustion technology. Considered waste composition is based on Turkish industrial waste generation data. This is the first study in the literature that environmental remediation cost of refinery and coke processing residues is obtained in line with the original calculation route by Extended Exergy Accounting methodology, i.e., artificial ways such as determination of environmental remediation cost by converting monetary cost of treatment system into its exergetic equivalent are avoided. Integrated gasification combined cycle is a commercially mature, technically well-known and state-of-the-art industrial treatment system, thus, the obtained environmental remediation cost result has the corresponding importance. Environmental remediation cost of refinery and coke waste combination is determined as 0.138 TJ/Ton and it is seen that resource consumption in required treatment processes for emitted CO2 and waste transportation are the largest constituents of environmental remediation cost. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Extended exergy; EEA; IGCC; Refinery waste; Coke processing waste; Environmental remediation cost; COMPLEX-SYSTEMS; ENERGY; PERFORMANCE; EFFICIENCY; SECTOR